Risk Stratifying and Prognostic Analysis of Subclinical Cardiac Implantable Electronic Devices Infection: Insight From Traditional Bacterial Culture - Gaofeng Lin; Tong Zou; Min Dong; Junpeng Liu; Wen Cui; Jiabin Tong; Haifeng Shi; Hao Chen; Jia Chong; You Lyu; Sujuan Wu; Zhilei Wang; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2021)
Background Subclinical infection of cardiac implantable electronic devices (CIEDs) is a common condition and increases the risk of clinical infection. However, there are limited studies focused on risk stratifying and prognostic analysis of subclinical CIED infection. Methods and Results Data from 418 consecutive patients undergoing CIED replacement or upgrade between January 2011 and December 2019 were used in the analysis. Among the patients included, 50 (12.0%) were detected as positive by bacterial culture of pocket tissues. The most frequently isolated bacteria were coagulase‐negative staphylococci (76.9%). Compared with the noninfection group, more patients in the subclinical infection group were taking immunosuppressive agents, received electrode replacement, or received CIED upgrade and temporary pacing. Patients in the subclinical infection group had a higher PADIT (Prevention of Arrhythmia Device Infection Trial) score. Univariable and multivariable logistic regression analysis found that use of immunosuppressive agents (odds ratio [OR], 6.95 [95% CI, 1.44–33.51]; P=0.02) and electrode replacement or CIED upgrade (OR, 6.73 [95% CI, 2.23–20.38]; P=0.001) were significantly associated with subclinical CIED infection. Meanwhile, compared with the low‐risk group, patients in the intermediate/high‐risk group had a higher risk of subclinical CIED infection (OR, 3.43 [95% CI, 1.58–7.41]; P=0.002). After a median follow‐up time of 36.5 months, the end points between the subclinical infection group and noninfection group were as follows: composite events (58.0% versus 41.8%, P=0.03), rehospitalization (54.0% versus 32.1%, P=0.002), cardiovascular rehospitalization (32.0% versus 13.9%, P=0.001), CIED infection (2.0% versus 0.5%, P=0.32), all‐cause mortality (28.0% versus 21.5%, P=0.30), and cardiovascular mortality (10.0% versus 7.6%, P=0.57). Conclusions Subclinical CIED infection was a common phenomenon. The PADIT score had significant value for stratifying patients at high risk of subclinical CIED infection. Subclinical CIED infection was associated with increased risks of composite events, rehospitalization, and cardiovascular rehospitalization.